Autograft immune content and survival in non-Hodgkin's lymphoma: A post hoc analysis. (June 2019) - Porrata, Luis F.; Inwards, David J.; Ansell, Stephen M.; Micallef, Ivana N.; Johnston, Patrick B.; Villasboas, Jose C.; Markovic, Svetomir N.
Highlights: The infusion of autograft immune effectors cells affect survival post-APHSCT. The autograft is viewed as an adoptive immune-therapy. The autograft supports the concept of autologous graft-versus-tumor effect. Abstract: The infusion of autograft absolute lymphocyte and monocyte counts affect survival in patients undergoing autologous peripheral hematopoietic stem cell transplantation (APHSCT). However, the specific autograft immune effector cells affecting survival post-APHSCT are unknown. Thus, we performed an ad hoc analysis from our published double-blind, randomized phase III clinical trial in non-Hodgkin's lymphoma (NHL) patients, looking at the infused autograft immune effector cells and their relationship with clinical outcomes post-APHSCT. Between December 2007 and October 2010, we performed a double-blind phase III randomized study registered with ClinicalTrials.gov, number NCT00566228. A total of 111 patients finished the trial and apheresis collection samples were analyzed for immune effector cells. Overall survival (OS) and progression-free survival (PFS) were calculated from the date of APHSCT. With a median follow-up of 82.8 months (range: 2.1–122.3 months), we identified by univariate analysis that the autograft numbers of macrophage type 1 (M 1), macrophage type 2 (M 2), dendritic cell type 1 (DC 1), dendritic cell type 2 (DC 2), myeloid-derived suppressor cells (MDSC), CD4+PD-1-, CD4+PD-1+, CD8+PD-1-, CD8+PD-1+, lymphocyte to monocyte ratio (A-LMR), NKp30, and KIR2DL2, were predictors for OS and PFS. Multivariate analysis revealed that A-LMR, MDSC, NKp30, KIR2DL2 and lactate dehydrogenase were independent predictors for OS. Independent predictors for PFS identified by multivariate analysis included DC1, MDSC, NKp30, CD4+PD-1- and M 2. Our findings indicate that the number of specific infused autograft immune effector cells affect survival ; thus providing a platform to develop an immunocompetent autograft with direct impact on clinical outcomes in NHL post-APHSCT.